Penggunaan Ragam Bahasa Mahasiswa Tingkat Awal dan Akhir UPN “Veteran” Jawa Timur di Media Sosial X: Use of Various Languages ​​of Early and Final Level Students of UPN "Veteran" East Java on Social Media - Alfianda, Muhammad Hengga; Solihah, Aisyah Farhatus; Hidayah, Talita Nur; Putri, Najwa Fellycia Amanda; Ramadhan, Abdurrahman Faiz Akbar (KIRANA : Social Science Journal, 2025)
This research aims to analyze the use of various languages ​​by initial and final level students at UPN Veteran East Java on social media X and its effects on social interaction. With the development of communication technology, social media has become the main platform for students to interact, share information and express themselves. The use of language on social media is influenced by many factors, including age, environment and level of education. In this context, freshmen and final year students have different backgrounds and experiences, which influence the way they communicate on digital platforms. The research method used is descriptive qualitative with data collection techniques in the form of observation. Data were analyzed to identify differences and similarities in the use of various languages ​​between the two groups of students. It is hoped that the results of this research will provide a deeper understanding of language dynamics among students, as well as the factors that influence their language choices on social media. These findings can also be a basis for developing better digital literacy among students and provide important insights into the dynamics of digital communication among the younger generation and their implications for the development of the Indonesian language in the modern era.